Economic openness and fiscal multipliers - Marco Riguzzi (University of Bern, Department of Economics, 2014)
This essay examines the implications of openness to trade, capital mobility, and exchange rate exibility for the fiscal multiplier. It presents a New Open Economy Macroeconomics model which is extended with the formation of 'deep habits' by individual households. Hereby, an inter-temporal substitution effect is constituted, which causes monopolistically competitive producers to move their markups counter-cyclically and generates a positive fiscal multiplier of private consumption. The main outcome is a mechanism elaborating that both openness to trade and exchange rate exibility limit the fiscal multiplier in equilibrium, and that capital mobility increases the fiscal multiplier in the short run. This dynamic model differs in its implications from a static model, such as the Mundell-Fleming model, and it is consistent with recent empirical findings.
Keywords: E12; E62; F4; 330; fiscal multiplier; openness to trade; capital mobility; exchange rate exibility